THE NATURE OF HYPNOTIC ANALGESIA: NEUROPHYSIOLOGICAL EVIDENCE AND FOUNDATIONS - Crawford, Helen J.; Knebel, Timothy; Vendemia, Jennifer M.C.; Horton, James E.; Lamas, Juan R. (Anales de Psicología / Annals of Psychology, 1999)
This paper reviews neurophysiological research (EEG, event-related potential, cerebral blood flow, functional Magnetic Resonance Imaging, and neurochemical) that supports the proposal that hypnotic analgesia is an active inhibitory process involving several brain systems mediating attentional and nociceptive processes. Even though the processes of hypnotic analgesia may be dissociated from conscious awareness and appear to be beyond volitional control, it is proposed that hypnotic analgesia depends on the activation of a supervisory, attention control system -involving the anterior frontal cortex- which then participates with other cortical and subcortical systems in the allocation of thalamocortical activities. Hypnotic analgesia affects the active allocation of attention and disattention associated with the anterior frontal region, as well as spatio-temporal aspects pain perception associated with the posterior cortical systems.